Library–faculty collaboration in the light of a business administration bachelor’s program –“A Scientific Wave” - Näverå, Elisabeth; Olsson, Anna Karin (Septentrio Conference Series, 2021)
This paper elucidates the process of creating and maintaining a successful librarian-faculty partnership which originally was intended as a quality improvement tool for a bachelor program in business administration at University West, Sweden. In 2012, after receiving criticism from the Swedish Council for Higher Education regarding the learning outcomes of students’ information literacy skillswithin the field of business administration, the process of regeneration started. A quality improvement process called “A Scientific Wave” was initiated to support the student's development regarding skills in critical and analytical approaches, presentation techniques and media and information literacy skills. The Scientific Wave includes different quality aspects and applies a holistic approach to improve educationquality and accentuate progression of knowledge throughout all courses of the program. Furthermore, work-integrated learning, WIL, is applied as an educational and pedagogical model throughout the program to reinforcethe link between work life and learning-theory and practice. Earlier research statesthat successful integration of media and information literacy in higher education should be based on close collaboration between librarians and discipline faculty, strategic anchoring and visualization in curriculums, syllabi, course objectives and examinations, and developed in line with the mission of the university. The Scientific Wave is here viewed as a co-creative continuous process based on the separate but still complementary skills of librarians and faculty to provide students with tools for critical and creative thinking in today’s digital society.